Межвидовые гибриды бычков семейства Gobiidae - Пинчук, В.И.; Страутман, И.Ф. (Вестник зоологии, 1977)
A sample of Gobius paganellus L. possessing some characters of Gobius cobitis P a l l. was caught in the Black Sea near Tuapse. Eight samples of adult hybrids of Neogobius kessleri (G u n t.) X Neogobius gymnotrachelus (K e s s I.) were caught in the Dniester estuary. The hybrids occupy an intermediate position between both parental species (closer to N. kessleri). Descriptions and dimensions of the fishes are given.